(untitled) (Journal of Partial Differential Equations, 2013)
We establish the existence, uniqueness and the blow-up rate of the large positive solution of the quasi-linear elliptic problem -_pu=λ (x)u^θ -1-b(x)h(u), in Ω, with boundary condition u=+∞ on Ω , where Ω R^N (N≥ 2) is a smooth bounded domain, 1